Identifikasi Isolat Phytophthora asal Kelapa dengan Amplifikasi Fragment Length Polimorfis (AFLP) - A. A. LOLONG (Buletin Palma, 2010)
Identification of Phytophthora Isolates from Coconut Origin Wite Amplification Fragment Length Polymorphic (AFLP)Coconut Bud rot and nutfall caused by  fungus are the major anddangerous diseases of coconut palm. Nutfall of nuts and death of the palms leading to the reduction of coconut production are some of the consequences of the diseases. Morphologically identification of the causal agents is very limited and need certain skill. Molecular analysis is a good method to accurately identify characterize the disease causing pathogens especially Phytophthora originated from coconut palm. AFLP is one the accurate reproducible methods providing uniformnity results. The research aimed to identify and characterize Phytophthora isolate causing but rot a nutfall diseases. A total of 14 isolates was tested by its AFLP and then by AFLP with specific primers. The identification results showed that the 14 tested isolates with ITS1/ITS4 had band profile on the size of 900 base pairs (bp) which is a specific band profile for P. Palmivora. Of the 16 combinations specific primer of AFLP, indicated primers eg E, H, and Q gave accurate and homolog results that is good for AFLP analysis. AFLP analyses for 14 isolates of  gave accurate results of the band diversity.